ANALISIS SUMBER DAN PENGGUNAAN DANA PERUSAHAAN DI SEKTOR PERBANKAN - B11106086, Sri Mulyati (Jurnal Manajemen Update, 2013)
This study aims to determine the use of fund assets are used to finance the company's banking operations are routine.In preparing this paper the author chose the title of the discussion" analysis of sources and uses of corporate funds in the banking sector". The method used is the method of direct writers,which means any changes in variable cost recorded in each - each account in the form of T,including changes in funding,profit and loss,as well as the sources and uses of funds. The author tries to discuss how to analyze sources and uses of funds,obstacles - obstacles that arise and an attempt to overcome these obstacles. Based on the results of the discussion,it appeared in 5 firms banking sector declined more funds than the source of the funds that had.